2009
DOI: 10.1177/030089160909500308
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Postoperative Irradiation in Patients with Newly Diagnosed WHO Grade III Anaplastic Gliomas

Abstract: Patients with WHO grade III anaplastic astrocytomas, oligodendrogliomas and oligoastrocytomas show favorable overall survival after postoperative radiotherapy compared with glioblastoma patients and should therefore be analyzed separately. Radiochemotherapy might further improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…21,23,24,30,31 Nomiya et al 21 analyzed survival outcomes and prognostic factors for 170 patients with AA and found that patients who underwent total or subtotal resection had a significantly more favorable prognosis than did patients who underwent partial resection or biopsy. Two other studies reported incremental improvements in overall median survival with increased extent of surgical resection among patients with histologically different anaplastic gliomas (pure AA vs anaplastic oligoastrocytoma vs AO).…”
Section: Extent Of Surgical Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,23,24,30,31 Nomiya et al 21 analyzed survival outcomes and prognostic factors for 170 patients with AA and found that patients who underwent total or subtotal resection had a significantly more favorable prognosis than did patients who underwent partial resection or biopsy. Two other studies reported incremental improvements in overall median survival with increased extent of surgical resection among patients with histologically different anaplastic gliomas (pure AA vs anaplastic oligoastrocytoma vs AO).…”
Section: Extent Of Surgical Resectionmentioning
confidence: 99%
“…Two other studies reported incremental improvements in overall median survival with increased extent of surgical resection among patients with histologically different anaplastic gliomas (pure AA vs anaplastic oligoastrocytoma vs AO). 23,30 Nagy et al 30 reported a median OS of 32 months after GTR, 36 months after subtotal resection, and 12 months after biopsy.…”
Section: Extent Of Surgical Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF expression in human glioblastomas is also correlated with vascular endothelial growth factor (VEGF) expression [16]. In the clinical setting, the histological grading is a key factor for predicting the biological behavior of gliomas and influencing the choice of therapies, particularly determining the use of adjuvant radiation and specific chemotherapy protocols [17,18]. However, to our knowledge, the exact relationship between histological grading and MIF expression in tumor cells has not yet been elucidated in sufficient detail.…”
Section: Introductionmentioning
confidence: 99%
“…For anaplastic gliomas, overall survival after standard treatment following primary diagnosis, including neurosurgical resection and postoperative radiotherapy, lies between 18 and 50 months [3]. However, also these patients develop tumor recurrences after primary diagnosis, and effective salvage treatments are required.…”
Section: Introductionmentioning
confidence: 99%